Wearable respiratory sensors for health monitoring - Zhifu Yin; Yang Yang; Cong Hu; Jinzhe Li; Boyu Qin; Xue Yang (NPG Asia Materials)
Abstract Real-time monitoring and early warning of human health conditions is an important function of wearable devices. Along with the development of the Internet of Things and the medical drive for early detection and treatment, wearable devices will become increasingly important in the future. Compared with traditional sensors, wearable sensors with mechanical softness and deformability are able to adapt to geometric nonlinearities and deformations caused by motion that occurs in application scenarios, thus ensuring stable and effective signal output under various complex working conditions. Various novel sensing materials have been developed for the detection of various biomarkers of respiration over the past few years. Here, we summarize the latest innovations in wearable respiratory sensors, highlighting the dominant sensing materials, designs, sensing mechanisms, and clinical implications. Finally, the future challenges and directions of wearable respiratory sensors are outlined toward promoting advancement in the field of wearable respiratory monitoring.